Mariví Romero, periodista taurina - Forneas, María Celia (Estudios sobre el Mensaje Periodístico, 2002)
This text will try to pay the debt (literary debt) I have with the bullfighting journalist Marivi Romero. In 1998, publishing date of my second book La crónica taurina actual. Un texto informativo literario y de opinión, I wanted to include her San Isidro´s 94 bullfighting chronics togheter with those of her fellows Vicente Zabala (ABC), Ignacio Alvárez Vara, Barquerito, (Diario 16), Javier Villán (El Mundo) and Joaquín Vidal (El Pais). Then, it was simply impossible. Now, when my third book Periodistas Taurinos Españoles del Siglo XIX is on sale, I am ready to analyse Mariví Romero´s bullfighting chronics published in La información de Madrid during Feria de San Isidro in 1994.